Effect of Smoking on Red Blood Cell Parameters: A Cross-sectional Study in a Divisional City of Bangladesh - Towhid, Shah Abdullah Al; Yousuf, Talha Bin; Begum, Roushon Ara (Journal of Monno Medical College, 2024)
Background: Several metabolic and biochemical processes, hormone secretion, and the haematological system are all affected by smoking. Numerous studies have found that smoking is associated with higher levels of haemoglobin concentration (Hb%), total red blood cell count (RBC), and red cell distribution width (RDW). Objectives: To study the RBC parameters in healthy male smokers and non-smokers among adults. Methodology: This research was carried out in the Department of Physiology of Sylhet MAG Osmani Medical College, from July, 2021 to June, 2022. A total of 200 participants were included with healthy adult smokers and age-matched healthy adult non-smokers. History and physical examinations were used to evaluate each individual. We measured height and weight, and calculated body mass index of the subjects. Calculations were made on cigarette smoking intensity and duration. Blood was collected to determine RBC parameters, such as total RBC count, haemoglobin level, haematocrit, mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobin concentration (MCHC) and red cell distribution width (RDW) by using Sysmex 500i automatic haematology analyzer (Japan). Results: Among the 200 participants, 100 were adult smokers and another 100 age-matched healthy adult non-smokers. The RBC indices were significantly elevated in smokers compared to non-smokers group: mean haemoglobin concentration (g/dl)+ standard deviation (SD) were 14.17 ± 2.13 versus 13.27 ± 1.39 respectively with p<0.001, mean haematocrit (HCT) (percent)+ SD were 41.60 ± 6.88 versus 39.13 ± 5.46 respectively with p=0.005, mean corpuscular volume (MCV) (fl) + SD 91.13 ± 8.86 versus 88.33 ± 5.58 respectively with p=0.033, mean corpuscular hemoglobin (MCH) (pg) + SD 31.16 ± 3.26 versus 30.05 ± 3.0 respectively with p=0.016 and mean red cell distribution width (RDW) (percent)+ SD 14.74 ± 1.63 versus 14.00 ± 1.57 respectively with p=0.001. However, RBC count (×106/μl) (4.60 ± 0.80 versus 4.46 ± 0.60; p=0.143) and mean corpuscular haemoglobin concentration (MCHC) (g/dl) (34.23 ± 2.11 versus 34.11 ± 2.32; p=0.707) did not differ significantly between smoker and non-smoker groups. There was no statistical difference between mild, moderate, and severe smokers, according to the study's variables. Conclusion: MCV, MCH, RDW, haematocrit, and haemoglobin concentration were all significantly higher in smokers. Journal of Monno Medical College December, 2023; 9 (2):41-46